Fleshing Out the Racial Undertones of Poverty for Canadian Women and their Families: Re-envisioning a Critical Integrative Approach - Gazso, Amber; Waldron, Ingrid (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This paper argues for re-envisioning a critical integrative approach to poverty in lone mother families. In order to substantiate our argument, we unpack the concept feminization of poverty by fleshing out its racial undertones. We also show how a gendered and racialized understanding of poverty in lone mother families is neutralized and/or erased in political and policy discourses and media.